2012
DOI: 10.3349/ymj.2012.53.1.118
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Needs of Breast Cancer Patients Relative to Survival Duration

Abstract: PurposeThe present study aims to evaluate the prevalence of unmet needs among breast cancer survivors, to assess the relationships between unmet needs and depression and quality of life, and to explore the extent to which unmet needs of breast cancer patients relate to the time elapsed since surgery.Materials and MethodsAmong 1,250 eligible patients who participated in the study, 1,084 cases (86.7%) were used for analysis. Clinicopathological and social parameters were reviewed and the Supportive Care Needs Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
89
2
12

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(114 citation statements)
references
References 28 publications
11
89
2
12
Order By: Relevance
“…Few other studies reported the same to be 40% in both the areas. 9,10,11,12 .The severity of psychosocial problems had statistically significant association with age, 2, 13, 14, advanced stages of illness, 14,15,16 duration of cancer, 14,7,17 and type of treatment received 18,17,11,19,20 which was in accordance with several other studies.…”
Section: Discussionsupporting
confidence: 89%
“…Few other studies reported the same to be 40% in both the areas. 9,10,11,12 .The severity of psychosocial problems had statistically significant association with age, 2, 13, 14, advanced stages of illness, 14,15,16 duration of cancer, 14,7,17 and type of treatment received 18,17,11,19,20 which was in accordance with several other studies.…”
Section: Discussionsupporting
confidence: 89%
“…While depression was found to be highest at diagnosis (Odle, 2011), depression during survivorship has not been studied adequately. During the follow-up care, survivors' psychological needs were often neglected (Park and Hwang, 2012). A main theme of depression among breast cancer survivors was the fear of breast cancer recurrence and metastasis (Pan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Pocos son los países que tienen dentro de sus sistemas de salud un programa psicooncológico bien estructurado que le permita a estas pacientes tener una visión más adaptativa de su enfermedad (26,27) . A pesar de que las sociedades han cambiado, las investigaciones relacionadas con los factores psicosociales (28) y familiares (29,30) que influyen en la capacidad de afrontamiento y el incremento de la calidad de vida del paciente y su familia no se han actualizado (21,22) . Por lo que el objetivo del presente estudio es identificar cual es el sentimiento más frecuente que presentan las pacientes con cáncer de mama al recibir el diagnós-tico de mama, cuáles son las estrategias de afrontamiento más utilizadas y los factores que pueden estar relacionados con dichas estrategias.…”
Section: Introductionunclassified